Access to Basic Education: Implications for the attainment of Sustainable Development Goals in Nigeria - AKOGUN, Alabelapo Kadri; ABOLADE, Sunday Babalola (Ilorin Journal of Education, 2023)
This paper discusses the issue of access to basic education and implications for the attainment of Sustainable Development Goals in Nigeria. In the process, it considers children’s access to basic education in the era of Millennium Development Goals (MDGs); and discusses what attention should be given to quality access to basic education, based on the United Nations declaration of 2030 in terms of Sustainable Development Goals. Most of the goals, including the educational goal of ensuring quality education (goal 4) are expected to be pursued substantially by 2030. The discussion features historical analysis of issues, making use of primary and secondary sources of data in the fashion of historical research. It was found that Nigeria was unable to attain the millennium development goal of free universal basic education by 2015 in spite of its intention to do so as expressed in the National Policy on Education. The paper concludes that with the necessary political will, Nigerian government should pursue more realistically, the issue of quality education which features as goal 4 of the SDGs. It is only then that other development goals would naturally lend themselves to easy implementation for the attainment of Sustainable Development Goals (SDGs) and consequently, robust national development by 2030.